Impact of Key Cooperative Variables on Performance of Cooperatives in Nepal - Kharel, Tikaram (Journal of Research in Education, 2025)
This paper examine the impact of Cooperative variables on the performance of selected cooperatives in Nepal. A sample of 400 members from primary cooperatives in Sudurpaschim Province was selected using stratified random sampling, with primary data gathered through a semi-structured questionnaire. Data analysis was conducted using with statistical tools such as correlation and regression analysis. The results show a significant positive relationship between professionalization, accountability, and cooperative performance. Additionally, participation and transparency have a positive but insignificant effect on performance, while legitimacy shows an insignificant negative relationship. The study concludes that cooperative performance is influenced by like legitimacy, participation, professionalization, accountability, and transparency. The research highlights the critical role in enhancing the quality of life for cooperative members, contributing to performance improvements. This study adds to the literature by identifying key elements that impact cooperative performance in a developing nation context.